Pengaruh Budaya Kerja terhadap Kinerja Perawat Rawat Inap pada Rumah Sakit Krakatau Medika Cilegon - Hafiz Nurrahman Sidiq; Firman Shakti Firdaus (Bandung Conference Series: Business and Management, 2024)
Abstract. This research is based on the observation that the conditions of work culture and the performance of nurses in the hospital are not yet optimal, thus requiring a deeper understanding of the relationship between these two variables. The objectives of this study are to determine: 1) the condition of the work culture at Krakatau Medika Hospital Cilegon. 2) the condition of the performance of inpatient nurses at Krakatau Medika Hospital Cilegon. 3) to examine how work culture influences the performance of inpatient nurses at Krakatau Medika Hospital Cilegon. The research methods employed include determination tests, simple linear regression tests, and t-tests (partial) with a quantitative approach. The study population consists of 160 inpatient nurses, with 61 respondents as the sample, using the simple random sampling technique. Data collection techniques involve questionnaires, interviews, observations, and literature reviews. The analysis results indicate that the hospital's work culture is assessed through four dimensions: discipline, openness, mutual respect, and cooperation. The research findings show that the work culture of inpatient nurses in the hospital falls into the high category. Additionally, the performance of inpatient nurses is also rated high based on five dimensions, including assessment, nursing diagnosis, intervention/planning, implementation, and evaluation. Furthermore, the analysis results reveal a positive influence between work culture and the performance of inpatient nurses. Thus, this study provides a better understanding of the relationship between work culture and the performance of inpatient nurses at Krakatau Medika Hospital Cilegon. The research is expected to offer in-depth insights and recommendations for enhancing the performance of inpatient nurses through the improvement of the work culture in the hospital. Abstrak. Penelitian ini didasari oleh pengamatan bahwa kondisi budaya kerja dan kinerja perawat di rumah sakit tersebut masih belum optimal, sehingga perlu adanya pemahaman yang lebih mendalam mengenai hubungan antara kedua variabel tersebut. Penelitian ini bertujuan untuk mengetahui: 1) bagaimana kondisi budaya kerja di Rumah Sakit Krakatau Medika Cilegon. 2) bagaimana kondisi kinerja perawat rawat inap di Rumah Sakit Krakatau Medika Cilegon. 3) mengkaji bagaimana pengaruh budaya kerja terhadap kinerja perawat rawat inap di Rumah Sakit Krakatau Medika Cilegon. Metode penelitian yang digunakan adalah uji determinasi, uji regresi linear sederhana, dan uji t (parsial) dengan pendekatan kuantitatif. Populasi yang diteliti adalah 160 perawat rawat inap, dengan 61 responden sebagai sampel dengan teknik simple random sampling. Teknik pengumpulan data meliputi kuesioner, wawancara, observasi, dan studi pustaka. Hasil analisis mendapatkan bahwa budaya kerja di rumah sakit dianalisis melalui empat dimensi: disiplin, keterbukaan, saling menghargai, dan kerjasama. Hasil penelitian menunjukkan bahwa budaya kerja perawat rawat inap di rumah sakit tersebut termasuk dalam kategori tinggi. Selain itu, kinerja perawat rawat inap juga dinilai tinggi berdasarkan lima dimensi yang meliputi pengkajian, diagnosa keperawatan, intervensi/perencanaan, implementasi, dan evaluasi. Selanjutnya hasil analisis menunjukkan adanya pengaruh positif antara budaya kerja dan kinerja perawat rawat inap. Dengan demikian, penelitian ini memberikan pemahaman yang lebih baik mengenai pengaruh antara budaya kerja dan kinerja perawat rawat inap di Rumah Sakit Krakatau Medika Cilegon. Penelitian ini diharapkan dapat memberikan wawasan mendalam dan rekomendasi untuk meningkatkan kinerja perawat rawat inap melalui peningkatan budaya kerja di rumah sakit.